A new production technique for rotameters and venturimeters - Tanyildizi, Vedat; Eren, Haydar (Elsevier Sci Ltd, 2006)
In this work, a simple and cheap production technique for the liquid and gas flow meters widely used in industry is presented. The technique is concerned with the production of the flowmeter case and simply employs the relative equilibrium property of a liquid in a container rotating with constant angular velocity. The liquid used is a special chemical solidifying during the process. Naturally, a tube with a paraboloidal inner surface is obtained and this tube can be used as the flowmeter case. A comparison of the flow rate computations shows that flowmeters with paraboloidal inner surfaces thus obtained provide, in fact, a slightly better approximation than the usual flowmeters with conical inner surfaces. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: rotameters; venturimeters; centrifugal casting technique